Development and Validation of the Health Anxiety Inventory (HAI) - Krishnamurthy V. S. (CV. Doki Course and Training, 2026)
Health anxiety has emerged as a major psychological concern in contemporary society due to increased exposure to online medical information, heightened awareness of diseases, and rapid dissemination of health-related content through digital media. Existing measures assessing health anxiety are predominantly developed within Western cultural contexts and may inadequately capture culturally specific illness beliefs and health-related behaviors observed among Indian adults. The present study aimed to develop and validate the Health Anxiety Inventory (HAI), a culturally grounded multidimensional instrument designed to assess health anxiety among adults. The scale was developed based on cognitive-behavioral and socio-cultural theoretical frameworks. An initial pool of 30 items across six dimensions was generated through literature review, expert consultation, and analysis of socio-cultural health beliefs. The dimensions included Anticipatory Health Worry, Bodily Sensation Monitoring, Catastrophic Interpretation, Reassurance Seeking and Healthcare Utilisation, Functional Impairment and Avoidance, and Socio-Cultural Health Beliefs. The inventory was administered to 183 college students selected through convenience sampling. Reliability analysis revealed excellent internal consistency (Cronbach’s α = .912). Item-total correlations ranged from .32 to .68, indicating satisfactory construct representation. Expert evaluations supported content validity, while theoretical coherence and statistical findings supported construct validity. The findings suggest that the HAI is a reliable and culturally relevant instrument suitable for assessing health anxiety among adults. The inventory may be useful in psychological assessment, counseling interventions, public mental health screening, and behavioral medicine research.